2021
DOI: 10.1523/jneurosci.2210-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Roles of Pallidal Neuron Subtypes in Regulating Motor Patterns

Abstract: Author contributions SC and BLB performed histological analysis. SC, QC, IYMC, HSX, YZ, HM, ZAA, and XD surveyed the intrinsic properties. QC, HMH, XD, YZ, and CJW examined the local connectivity. AP, QC, SR, and NJJ conducted the behavioral studies. IYMC developed the machine learning analysis pipeline. YC and SMB provided expertise for neuron classification. CSC wrote the manuscript with input from all co-authors. All authors reviewed and edited the manuscript. CSC designed, directed, and supervised the proj… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 151 publications
(198 reference statements)
3
38
1
Order By: Relevance
“…Optogenetic dissection of the indirect pathway has revealed that the activation of striatal iSPNs has a locomotor-suppressing effect, an effect replicated in several studies where the optogenetic manipulation was performed in the dorsomedial striatum (Cui et al, 2021;Kravitz et al, 2010;Isett et al, 2022). Conversely, the inhibition of iSPNs in the dorsolateral striatum had movement promoting effects (Cui et al, 2021), although the underlying circuitry remains unclear. Optogenetic somatic manipulations of iSPN activity will influence local iSPN collaterals in addition to downstream projections.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Optogenetic dissection of the indirect pathway has revealed that the activation of striatal iSPNs has a locomotor-suppressing effect, an effect replicated in several studies where the optogenetic manipulation was performed in the dorsomedial striatum (Cui et al, 2021;Kravitz et al, 2010;Isett et al, 2022). Conversely, the inhibition of iSPNs in the dorsolateral striatum had movement promoting effects (Cui et al, 2021), although the underlying circuitry remains unclear. Optogenetic somatic manipulations of iSPN activity will influence local iSPN collaterals in addition to downstream projections.…”
Section: Discussionmentioning
confidence: 86%
“…Further, the indirect pathway has been proposed to be involved in negative reinforcement (Kravitz et al, 2012). Optogenetic dissection of the indirect pathway has revealed that the activation of striatal iSPNs has a locomotor-suppressing effect, an effect replicated in several studies where the optogenetic manipulation was performed in the dorsomedial striatum (Cui et al, 2021;Kravitz et al, 2010;Isett et al, 2022). Conversely, the inhibition of iSPNs in the dorsolateral striatum had movement promoting effects (Cui et al, 2021), although the underlying circuitry remains unclear.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations